Wearable sensors for monitoring chronic kidney disease - Sanggil Han; Shunsuke Yamamoto; Chan-Young Jung; Do Young Jin; Taegyu Lee; Jun-Seob Kim (Communications Materials, 2024)
Abstract Wearable sensors have evolved significantly, making personalized medicine and real-time disease management possible. However, current digital healthcare is limited to only certain diseases, such as diabetes, due to the lack of mature technologies that can detect small biomolecules. In particular, despite the early detection of chronic kidney disease (CKD) being significant in preventing life-threatening end-stage kidney disease, the development of wearable sensors for CKD monitoring is still in the early stages. In this Perspective, we propose a wearable digital healthcare concept for non-invasive, continuous CKD monitoring, discuss optimal biofluids, biomarkers and bioreceptors to create a wearable CKD sensing platform, and provide insight into potential challenges faced by the technology as well as opportunities.